(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
In this article, the translation of Shakespeare’s works from the original had a direct impact on the formation of an approach to the spiritual heritage of the creator based on new criteria. In this process, the role of the talented poet and translator Jamal Kamal should be noted. With a proper understanding of the complex aspects of translation, his approach to the text, and his skill in expressing the spirit of the playwright’s era should be recognized as a product of great poetic creativity.